ANALISIS EFISIENSI LABA PADA INDUSTRI PERBANKAN SYARIAH DI INDONESIA DENGAN PENDEKATAN STOCHASTIC FRONTIER APPROACH (SFA) - Suhel Suhel (Jurnal Ekonomi Pembangunan, 2011)
This research is to analyze profit eficiency at Islamic Banking Industry in Indonesia, by using Parametric Stochastic Frontier Approach (SFA). A  purpose to wish influence analysis factor input and output to profit efficiency at Islamic Banking Industry in Indonesia  The object of this research is Commonly  Islamic Banking/ Bank Umum Syariah (BUS) that has operated at least since 2005. This research is using data panel to measure efficiency during 2005- 2009 period.The data used is data of quarterly bank unit from financial report of Islamic Banking, there are contain the data of total financing, earnings, current  assets, cost of employee, fixed assets, total deposits,  From the calculation, has found that during 2005 – 2009 period, Islamic Banking Industry has average of profit eficiency level about 93,41 percent, that is below  the 100 percent. Even though, the trend  shows  that the condition is more efficient.  The values shows that the existence of Islamic Banking Industry relatively has a good performance. Keywords: Profit Efficiency, Islamic Banking, Stochastic Frontier Approach